Effectiveness of landmark- and semi-landmark-based geometric morphometric to identify four species of Culex mosquitoes in Thailand (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This research aims to study the effectiveness of landmark- and semi-landmark-based geometric morphometric (LMSL) in the identification of four Culex vectors, namely, C. quinquefasciatus, C. visnui, C. sitiens, and C. whitmorei in Thailand and also compared the potential between LMSL and the landmark-based geometric morphometric method (LM).Materials and Methods: The overall size of the wing sample was estimated by the centroid size. Shape variables were computed as principal components of the “partial warp” calculated after generalized procrustes analysis of raw coordinates. Discriminant analysis of the canonical variables performed to explore the shape dissimilarity between Culex species has been shown as a factor map and to calculate the Mahalanobis distance. Size and shape differences based on pairwise Mahalanobis distances were tested using non-parametric methods (1,000 cycles) with Bonferroni correction at a p-value of